4. OPTIMIZATION OF M-TESE TECHNIQUE FOR PATIENTS WITH NON-OBSTRUCTIVE AZOOSPERMIA AND SMALL TESTES (Vietnam Journal of Community Medicine, 2024)
Introduction: Non-obstructive azoospermia (NOA) is a severe and complex cause of male infertility. Intracytoplasmic sperm injection (ICSI) combined with microdissection testicular sperm extraction (m-TESE) offers the possibility of biological fatherhood for NOA patients. However, the sperm retrieval rate (SSR) using m-TESE is typically only around 30–50%. Currently, there is no universally effective treatment method to enhance the SSR before undergoing m-TESE surgery. Therefore, optimizing the m-TESE technique, especially for NOA patients with small testes, may improve the chances of successful sperm retrieval. Objective: The study aims to optimize the m-TESE technique for NOA patients, particularly those with small testes, to increase the chance of sperm retrieval and improve reproductive support outcomes.Method: Analyzing and synthesizing studies on mTESE techniques and evidence from reputable medical organizations such as the American Urological Association (AUA), the European Association of Urology (EAU), and the American Society for Reproductive Medicine (ASRM).Results: To improve the sperm retrieval rate of m-TESE, it is necessary to select experienced surgeons, prioritize larger testes, and avoid varicocele. Using surgical magnification of 18 to 25 times to retrieve larger, more opaque, and whiter seminiferous tubules with a diameter of 0.3 mm or more. Combining both mechanical and enzymatic methods in sample processing can increase the effectiveness of sperm retrieval and improve sperm motility without affecting fertilization rates or embryo quality.Conclusion: Optimizing the m-TESE technique can increase the chance of sperm retrieval for NOA men, especially those with small testes..
Keywords: Optimizing m-TESE technique, non-obstructive azoospermia (NOA), small testes, sperm retrieval rate (SSR), ICSI.